Health-related quality of life of HIV patients with comorbidities of hypertension or diabetes in Ghana - Owusu, Richmond; Kwarteng, Emmanuel Bugyei; Bawua, Serwaa Akoto; Otoo, Desmond Dzidzornu; Nonvignon, Justice (Frontiers in Public Health, 2024)
BackgroundClinical studies, particularly in the context of HIV/AIDS, have utilized health-related quality of life (HRQoL) and health state utility values to assess both clinical and economic implications. Improvement in HIV management with antiretroviral therapy (ART) has coincided with an increased morbidity of chronic conditions such as diabetes and hypertension among people living with HIV. The study offers empirical evidence establishing a link between HIV, comorbidities like hypertension and diabetes, and their collective impact on HRQoL.MethodsA cross-sectional quantitative study among 418 HIV patients in three regions of Ghana in the Savannah, Middle Belt, and Coastal belt. Face-to-face interviews were conducted using EuroQol-5 Dimensions-5 Levels (EQ-5D-5L) in combination with EuroQol-Visual Analog Scales (EQ-VAS). Ugandan EQ-5D-5L value set was used for computing the utility values. Patients' socio-demographic and clinical data were obtained from medical records and analyzed descriptively. Mann-Whitney U and Kruskal Wallis tests were used to evaluate the relationship between patient socio-demographic and clinical variables and health status.ResultsOverall median utility value was 0.93(IQR=0.79, 1.00) from the EQ-5D index and 90 (IQR = 80, 100) from the EQ-VAS scores. Prevalence of hypertension and diabetes were 9.1% and 2.4% respectively. There was significant difference in EQ-VAS score between HIV patients with hypertension and those without hypertension (z = 2.146 p = 0.032). There was also a significant difference in the EQ-VAS scores (z = 2.381, p = 0.017) of patients with diabetes and those without diabetes. Region, sex, age, education, marital status, employment status, place of residence, monthly income level, duration of infection, adherence to ART, and other illness were significantly associated with EQ-5D-5L utility and EQ-VAS scores at 0.05 significant level.ConclusionHRQoL among HIV positive individuals in Ghana was high. Comorbidities such as hypertension or diabetes had nuanced effects on perceived health status. A patient-centered, multidisciplinary approach to HIV care should be adopted considering regional differences and the presence of comorbidities.